The ASTI Knowledge (AsK) network-an improved intranet for the Advanced Science and Technology Institute - Retamar, Alvin E. (University of the Philippines Diliman, 2004)
An Intranet is defined as "a Local Area Network (LAN) constructed as internal website and secured behind company firewalls". Simply put, it is an internal Internet accessed only by people within the organization. As proof of its tremendous uptake, a reported 64 billion dollars worth of investment in company intranets was spent in 2001. The Advanced Science and Technology Institute's (ASTI) current Intranet, the ASTI InfoSys, has existed for several years but it has not been able to realize its true potential. The ASTI InfoSys does not fully perform the functions it's supposed to do as a knowledge management tool in terms of sharing, storing, and retrieval of knowledge and information. It is for this reason that the ASTI Knowledge Network, or simply ASK, has been proposed. This project proposal has the following objectives : (1) improve upon ASTI's current Intranet to be more responsive to its personnel's needs (2) create better exchange, storage and retrieval of knowledge and information within the institute (3) provide a useful model that can be used or applied in the Intranet efforts of other entities. The proposed ASK network will have primary significance to ASTI since the institute will be its direct beneficiary. Aside from ASTI, the project has significance to other entities that have existing Intranets or those that are planning to put up one. In order to work out the necessary data and information required to sufficiently answer the identified problem, stakeholder interviews, informal interviews and actual use of the system will be conducted. For the stakeholder interview, 20 personnel from various project teams were selected. The Background Interview revealed that the primary objective of the ASTI InfoSys is to achieve the "Paperless Office" model by automating office processes. In this regard, the ASTI InfoSys is very effective. However, the same thing cannot be said for the Knowledge Management sections of the Intranet. This is evidenced by the lack of interest from users on this area of the Intranet. In light of this, there is a need to strengthen the KM aspect of the Intranet by enjoining the staff in its development. From the Stakeholder Interview, it was found out that ASTI staff perform routine and non-routine activities that require varying knowledge and information. Furthermore, ASTI personnel do not want every bit of information placed in the Intranet, only standard information such as reference materials. ASTI personnel view the Internet as a section of the Intranet where information of any kind can be found. They don't want AsK to be a duplication of other sources of information. The Intranet should co-exist with these sources of information by directing users to these sources. ASTI staff want AsK to be organized, easy to search, cross referred between sections and should contain the following areas : Reference Materials, Training Materials, Best Practices, Applications and Tools, Project Matters, Project Documentation, Office Rules and Regulations. A future consideration for ASTI and the Department of Science and Technology is to deploy an Extranet which will connect all DOST agencies in all twelve regions of the country. This extranet will allow DOST agencies to pursue collaborative work and easily share information.